INTRODUCTION TO GASTRODIPLOMATION OF ASEAN MEMBER STATES TO STUDENTS OF SMKN 30 JAKARTA THROUGH WEBINAR ACTIVITIES WITH THE MINISTRY OF FOREIGN AFFAIRS - Muhammad Kevin Muhfly Alfath; Muhammad Kholid Alfina (Jurnal Scientia, 2023)
Gastrodiplomation is a word adopted from Gastronomy that does not have a similar meaning and meaning to culinary. The government in every country created an official program to introduce its domestic cuisine to the international world through diplomacy. Currently, culinary is one of the important factors in attracting the attention of the world community to travel to various countries, in the current era of globalization information about the culinary of a country it is very easy and fast to access, from a wide variety of social media platforms such as Instagram, Facebook, Twitter and so on. With this phenomenon, we held community service activities to introduce gastrodiplomation to students in Indonesia, especially in the Jakarta area because Jakarta as The capital city of the Republic of Indonesia, students must know that this activity is one of the diplomatic activities, namely gastrodiplomation. We held a webinar, "Culinary and Culture (Gastrodiplomacy) as Forming Harmony Between Asean Countries" at the State Vocational High School 30 Jakarta majoring in food management which aims to educate students regarding gastrodiplomation, public diplomacy, and soft power diplomacy carried out by ASEAN member states, this webinar was attended by 47 students of SMKN 30 Jakarta majoring in food management. The material presented in this webinar is (1) Introduction to public diplomacy and soft power diplomacy, (2 ) Introduction to Gastrodiplomation and examples of gastrodiplomation activities carried out by several ASEAN member states. In this webinar activity, pre-tests and post-tests are carried out to determine the level of knowledge about gastrodiplomation and the influence of the webinar on students.